Inoculation with Mycorrhizal Fungi and Other Microbes to Improve the Morpho-Physiological and Floral Traits of Gazania rigens (L.) Gaertn - Ishan Saini; Ashok Aggarwal; Prashant Kaushik (Agriculture, 2019)
In the present analysis, we evaluated the effect of different microbial inoculants on growth and floral responses of Gazania rigens (L.) Gaertn. Two prevailing arbuscular mycorrhizal fungi (AMF) i.e., Funelliformis mosseae and Acaulospora laevis, along with Trichoderma viride and Pseudomonas fluorescens, were examined in a pot experiment. Independent roles of these four microbes and their different combinations were used in sixteen treatments of G. rigens. The experiment was conducted in a polyhouse with five replicates per treatment in a randomized complete block design. The results of microbial inoculants were very effective for growth yield and flowering response over the control. Early flowering was noted in the combination of F. mosseae, A. laevis and P. fluorescens, which also showed the best results for flower head size, flower fresh and dry weight, total chlorophyll, carotene and phosphorus content. Arbuscular mycorrhiza (AM) root colonization (%) and AM spore number were also the highest for the same treatment, whereas the number of leaves, number of buds and root length were maximum in the combined treatment (F. mosseae + A. laevis + T. viride + P. fluorescens). Overall, this study proposes that growers should consider microbial inoculants for the better yield and flower quality of G. rigens.